Mapping cones of positive maps - Størmer, Erling (MATHEMATICA SCANDINAVICA, 2011)
We study mapping cones of positive maps of $B(H)$ into itself, i.e., cones which are closed under composition with completely positive maps. As applications we obtain characterizations of linear functionals with strong positivity properties with respect to so-called symmetric mapping cones, with special emphasis on separable and PPT states.